BindingDB Entry 8653: Indazole and indole derivatives as inhibitors of retinoic acid related orphan receptor gamma (ROR gamma) for the treatment of immune-related diseases - BindingDB (BindingDB, 2020)
Small molecule binding data for protein Nuclear receptor ROR-gamma (RORC), Uniprot P51449 and Q6I9R9